Internet usage and information seeking behaviour of students conducting history projects: determining the need of a digital library for historical resources - Abdullah, Abrizah; A.N, Zainab (Persatuan Pustakawan Malaysia, 2005)
This paper reports the results of a user study done at the formative stage of development of a collaborative resource development (CoreDev) digital library for Malaysian historical resources by collaborating partners. CoreDev aims to provide an electronic system to help students obtain information on local history; collect, store and organize information in digital format; publish and share electronic resources. While most digital library projects were driven by technology development and research, there has been little investigation into how to develop a creative, working community around a digital library. This paper presents preliminary findings on students' readiness and receptivity to participate in the building of the digital library as content providers and developers, and their motivation and willingness to collaborate and share digital resources, as well as their understanding of their role in the collaborative digital library environment. Our findings indicate the feasibility of implementing the digital library for Malaysian schools. Series of surveys and interviews have led to rich findings of the students' and teachers' concerns and priorities regarding the digital library. Insights from these descriptions will then be used to establish a set of framework and design principles that could be used in designing our digital library.